Animal models for HIV/AIDS research - Hatziioannou, Theodora; Evans, David T. (Nature reviews. Microbiology, 2012)
Key Points Animal models are essential for testing antiretroviral drugs to treat HIV infection of humans and for acquiring the basic scientific knowledge that will ultimately be needed to develop a safe and effective vaccine against HIV-1. Owing to the narrow host range of HIV, HIV-1 infection of mice that have been reconstituted with a human immune system (humanized mice) and simian immunodeficiency virus (SIV) infection of macaques are used as surrogate models for studying HIV-1 infection of humans. There is no single animal model for AIDS, but rather a collection of host species and viruses that can be used depending on the question to be addressed. A number of humanized mouse models have been developed using different genetic backgrounds and engraftment with various human tissues. Whereas humanized mice make it possible to model HIV-1 infection of human cells in vivo and to design studies using genetically identical animals, these models are limited in their ability to replicate the effects of HIV-1 on non-haematopoietic tissues and to recreate basic features of HIV-1 disease in humans. Infection of Asian macaques with certain SIV or simian–human immunodeficiency virus (SHIV) recombinants results in gradual CD4 + T cell depletion and progression to AIDS, similar to HIV infection of humans. Thus, SIV and SHIV infection of macaques are currently the best, most widely accepted models for AIDS research. Genetic differences between macaque species, and in some cases between geographically distinct populations of the same species, can dramatically affect the outcome of SIV and SHIV infections and are important considerations in the use of these models. There is now considerable interest in engineering HIV-1 to overcome the barriers to HIV-1 replication in macaques. These barriers are imposed by the apolipoprotein B-editing catalytic subunit-like 3 (APOBEC3) proteins, by tripartite-motif-containing protein 5 (TRIM5) variants and by tetherin, all of which are HIV restriction factors. The development of minimally modified simian-tropic strains of HIV-1 that can reproducibly cause disease in macaques might eventually allow direct efficacy testing of antiretroviral drugs and vaccines in non-human primates. Although it may never be possible for a single animal model to recapitulate all of the features of HIV-1 infection of humans, there have been great advances in the development of small-animal and non-human primate models, as well as in the development of recombinant challenge viruses. Here, the authors review the advantages and disadvantages of the different animal models of HIV/AIDS with respect to their use in the preclinical development of vaccines and antiretroviral therapies. The AIDS pandemic continues to present us with unique scientific and public health challenges. Although the development of effective antiretroviral therapy has been a major triumph, the emergence of drug resistance requires active management of treatment regimens and the continued development of new antiretroviral drugs. Moreover, despite nearly 30 years of intensive investigation, we still lack the basic scientific knowledge necessary to produce a safe and effective vaccine against HIV-1. Animal models offer obvious advantages in the study of HIV/AIDS, allowing for a more invasive investigation of the disease and for preclinical testing of drugs and vaccines. Advances in humanized mouse models, non-human primate immunogenetics and recombinant challenge viruses have greatly increased the number and sophistication of available mouse and simian models. Understanding the advantages and limitations of each of these models is essential for the design of animal studies to guide the development of vaccines and antiretroviral therapies for the prevention and treatment of HIV-1 infection.